Queering reproductive access: reproductive justice in assisted reproductive technologies - Michelle W. Tam (BMC, 2021)
Abstract Background Advancements in assisted reproductive technologies (ART) and policy development have enabled more people to have biologically related children in Canada. However, as ART continues to focus on infertility and low fertility of heterosexual couples, ART access and research has been uneven towards meeting the reproductive needs of lesbian, gay, bisexual, transgender, queer, two-spirit, intersex, and asexual (LGBTQ2SIA +) people. Furthermore, experiences of reproduction are impacted by intersectional lived realities of race, gender, sexuality, and class. This commentary utilizes a reproductive justice (RJ) framework to consider reproductive access for LGBTQ2SIA + Black, Indigenous, and people of colour (BIPOC), while simultaneously engaging through a critical lens RJ has on ART. An RJ framework considers the constitutive elements of reproductive capacity and decision making that are not often at the forefront of reproductive health discussions. Additionally, this commentary discusses reproductive rights violations and reproductive violence such as coerced and forced sterilizations that have and are currently occurring in Canada. This article considers systems of access and structures of regulation that seek to control the reproductive capacities of marginalized communities, while empowering accessibility and upholding white supremacy and heteronormativity. In thinking through research and access in ART, who are ART users and whose reproduction is centered in research and access in Canada? Conclusion A reproductive justice framework is urgently needed to address inequities of sexual and reproductive health access in Canada.